2023
DOI: 10.3390/plants12081603
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Clustering and Classification of Coffee Leaf Diseases Based on an Extended Kernel Density Estimation Approach

Abstract: The current methods of classifying plan disease images are mainly affected by the training phase and the characteristics of the target dataset. Collecting plant samples during different leaf life cycle infection stages is time-consuming. However, these samples may have multiple symptoms that share the same features but with different densities. The manual labelling of such samples demands exhaustive labour work that may contain errors and corrupt the training phase. Furthermore, the labelling and the annotatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Disease symptoms look symmetric at different stages of infection, with the possibility of overlapping symptoms appearing on the same leaf. So, the wide variety of symptom characteristics in qualitative and quantitative terms makes it very challenging to collect disease samples (Hasan et al 2023). Li et al (2022a, b, c) proposed a lightweight network based on copy-paste and semantic segmentation for accurate disease region segmentation and severity assessment.…”
Section: Plant Disease Identificationmentioning
confidence: 99%
“…Disease symptoms look symmetric at different stages of infection, with the possibility of overlapping symptoms appearing on the same leaf. So, the wide variety of symptom characteristics in qualitative and quantitative terms makes it very challenging to collect disease samples (Hasan et al 2023). Li et al (2022a, b, c) proposed a lightweight network based on copy-paste and semantic segmentation for accurate disease region segmentation and severity assessment.…”
Section: Plant Disease Identificationmentioning
confidence: 99%
“…By combining the strength of different models, the stage wise ensemble was able to achieve improved accuracy and classification performance Some studies focused specifically on targeting class imbalances, such as the work of Hasan et al [14]. In their study, the authors used a kernel density estimation (KDE) approach for automated clustering and classification.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Approaches including Few Shot Learning, modifications to existing stateof-the-art architectures, ensemble learning and guided learning were used to achieve high accuracy on different datasets. While [14] worked on a deeper analysis of class overlapping and their segregation using a Kernel Density approach prior to using a convolutional network for a guided take on imbalanced classes, others focused entirely on pushing the capabilities of the convolutional networks achieving a maximum accuracies of 99.07 and 99.87% using concatenated and transfer learning models for 5 and 4 class classification. The computational costs and limited control over feature extraction pose significant challenges.While convolutions are indeed a powerful mechanism for feature extraction, hand crafted features provide a complementary interpretation of complex features and textures for better explainability of underlying decision making process if used alongside CNN.…”
Section: E Comparison With Existing Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Clustering perspective: Models are built by an analysis of intra-class differences. Representative algorithms based on traditional features include: Yu et al [19] constructed a K-means model to analyze intra-class differences and achieve clustering; Padol et al [20] established an SVM to cluster different disease images; Rani et al [21] enhanced clustering accuracy by adding SVM on top of the K-means algorithm; Trivedi et al [22] established a model from the perspective of a color histogram for image analysis; Faithpraise et al [23] established a K-means model for disease classification from a clustering perspective; Tamilselvi et al [24] used unsupervised machine-learning algorithms to cluster based on color features; and Hasan et al [25] proposed an extended kernel-density-estimation approach to analyze disease morphology. On the other hand, representative algorithms based on deep feature extraction mainly include: Yadhav et al [26] obtained clustering features based on the CNN model with optimized activation functions; Bhimavarapu et al [27] fused PSO and CNN algorithms to extract multi-dimensional features; Hatuwal et al [28] experimentally demonstrated the capabilities of random forest, KNN, SVM, and CNN for clustering; Pareek et al [29] established a 1D-CNN model for clustering based on image segmentation; Mukti et al [30] achieved plant-disease detection based on multiple iterations of ResNet; Li et al [31] analyzed plant diseases through the construction of the model ensemble with inception module and cluster algorithm; Türko glu et al [32] used deep networks to extract disease image features and analyze differences between classes; and Ramesh et al [33] constructed a model from the perspective of image and machine learning to achieve disease classification.…”
Section: Introductionmentioning
confidence: 99%